2022
DOI: 10.5114/bta.2022.116208
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency adventitious shoot organogenesis from in vitro stem explants of Scutellaria araxensis Grossh

Abstract: The present study introduced an in vitro shoot organogenesis protocol for the medicinal plant Scutellaria araxensis (Lamiaceae). Stem, leaf, and petiole explants were cultured in half-strength Murashige and Skoog (MS) medium containing different concentrations of 6-benzylaminopurine (BAP) alone or in combination with thidiazuron (TDZ), indole-3-butyric acid (IBA), or α-naphthalene acetic acid. Callus formation occurred from stem and petiole explants in most cultures; however, in leaf explants, it was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Nevertheless, it should be noted that, as shown by other authors, the process of indirect shoot organogenesis can be carried out using various combinations of phytohormones. According to Gharari et al [ 19 ], stem explants of S. araxensis allowed efficient shoot organogenesis through the callus stage, and obtaining up to 18 new shoots per explant on medium containing 0.5 mg × dm −3 BAP in addition to 0.5 mg × dm −3 IBA. Hwang et al [ 20 ] reported that callus induction in S. baicalensis occurred in the presence of 1-Naphthaleneacetic acid (NAA) 1 mg × dm −3 plus BAP mg × dm −3 , while Trivedi et al [ 21 ] showed that relatively high concentrations of TDZ (4 mg × dm −3 ) stimulated this process, and subsequently NAA 1 mg × dm −3 was sufficient for shoot regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be noted that, as shown by other authors, the process of indirect shoot organogenesis can be carried out using various combinations of phytohormones. According to Gharari et al [ 19 ], stem explants of S. araxensis allowed efficient shoot organogenesis through the callus stage, and obtaining up to 18 new shoots per explant on medium containing 0.5 mg × dm −3 BAP in addition to 0.5 mg × dm −3 IBA. Hwang et al [ 20 ] reported that callus induction in S. baicalensis occurred in the presence of 1-Naphthaleneacetic acid (NAA) 1 mg × dm −3 plus BAP mg × dm −3 , while Trivedi et al [ 21 ] showed that relatively high concentrations of TDZ (4 mg × dm −3 ) stimulated this process, and subsequently NAA 1 mg × dm −3 was sufficient for shoot regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, only 2.1 shoots per explant were obtained on substrate with GA 3 . The latter is generally known for its effect in the direction of shoot elongation [ 19 ], and only caused the development of two axillary buds present on the explant, with the length of the resulting shoots being greater compared to those obtained on the other media. Stem elongation in the presence of GA 3 also resulted in the development of an average of one internode more on the shoot compared to the other PGRs applied.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the values of the latter were the highest on the MS + BAP 2 medium (statistically significant compared to the other media), which was due to the simultaneous presence of callus tissue and shoots in the structure of the regenerants (Figure 2H). Gharari et al [18] pointed out the high effectiveness of BAP in combinations with various concentrations of TDZ, IBA, and NAA in the regeneration of Scutellaria araxensis, concluding that the best effect in indirect shoot organogenesis was achieved with the combination of BAP and TDZ. According to a study by Ozdemir et al [14] on S. orientalis subsp.…”
Section: In Vitro Culture Analysismentioning
confidence: 99%
“…In addition, it is necessary to consider the interactions between the genotype, type, and PGR concentration, as postulated by Dyduch-Siemińska [45] and confirmed by the results of Gharari et al [46], where shoot organogenesis through the callus stage allowed for obtaining a very high number of shoots, reaching up to 18 per explant in S. araxensis, and for the species we studied, S. baicalensis, the maximum was 5.8. At the same time, it is worth noting that different skullcap species, i.e., Scutellaria araxensis [18], Scutellaria baicalensis [20], Scutellaria bornmuelleri [46], and Scutellaria orientalis subsp. bicolor [14], exhibited a similar response to the applied MS medium without phytohormones.…”
Section: In Vitro Culture Analysismentioning
confidence: 99%
See 1 more Smart Citation